2003
DOI: 10.1093/jn/133.10.3298s
|View full text |Cite
|
Sign up to set email alerts
|

Black Tea Consumption Reduces Total and LDL Cholesterol in Mildly Hypercholesterolemic Adults

Abstract: Despite epidemiological evidence that tea consumption is associated with the reduced risk of coronary heart disease, experimental studies designed to show that tea affects oxidative stress or blood cholesterol concentration have been unsuccessful. We assessed the effects of black tea consumption on lipid and lipoprotein concentrations in mildly hypercholesterolemic adults. Tea and other beverages were included in a carefully controlled weight-maintaining diet. Five servings/d of tea were compared with a placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 33 publications
4
100
0
Order By: Relevance
“…Phenolics, such as polyphenols and the subgroup flavonoids, are powerful antioxidants capable of impacting favourably on CHD risk factors. Flavonoids are shown to prevent the oxidation of LDL (Davies et al, 2003), reduce clotting and improve coronary vasodilation (Mojži-šová and Kuchta, 2001); while plant polyphenols, such as those in tea and cocoa, increase plasma antioxidant levels (Weisburger, 2001). Black tea appears to have a greater impact on ex vivo lipoprotein oxidation than green tea (Hodgson et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolics, such as polyphenols and the subgroup flavonoids, are powerful antioxidants capable of impacting favourably on CHD risk factors. Flavonoids are shown to prevent the oxidation of LDL (Davies et al, 2003), reduce clotting and improve coronary vasodilation (Mojži-šová and Kuchta, 2001); while plant polyphenols, such as those in tea and cocoa, increase plasma antioxidant levels (Weisburger, 2001). Black tea appears to have a greater impact on ex vivo lipoprotein oxidation than green tea (Hodgson et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Human studies have shown that black tea flavonoids improve coronary circulation (Hirata et al, 2004) and attenuate endothelial disfunction (Duffy et al, 2001), although the latter may be influenced by individual variation in flavonoid metabolism (Hodgson et al, 2006). Secondly, tea flavonoids have also been shown to reduce low-density lipoprotein (LDL) cholesterol by 11.1% (Davies et al, 2003). Thirdly, in vitro and animal studies have revealed effects that go beyond antioxidant capacity, for example, reduced expression of endothelial adhesion molecules (Ludwig et al, 2004), stimulation of an anti-inflammatory response (Lin et al, 1999), and gene expression favouring improved smooth muscle function (Kim and Moon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Results for malondialdehyde were inconsistent as well: some investigations indicating a negative relation between tea and MDA (Freese et al, 1999;Hirano-Ohmori et al, 2005;Nagao et al, 2005), others showing no significant relationship (Rumpler et al, 2001;Davis et al, 2003).…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…The activity of antioxidant enzymes or oxidative status of the serum were improved by tea intervention in some studies (Serafini et al, 1996;Nakagawa et al, 1999;Leenen et al, 2000;Sung et al, 2000;Young et al, 2002), but remained unchanged in the others (Van Het Hof et al, 1997;Princen et al, 1998;Freese et al, 1999;Miura et al, 2000;Davis et al, 2003;Henning et al, 2004;Davis et al, 2005).…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…While moderately high levels of tea consumption (more than four cups per d) may reduce CVD risk, the effects of tea consumption on serum lipoproteins are not clearly established (218,219) . One small, placebo-controlled study reported a 3·8 % reduction in serum total cholesterol and a 7·5 % reduction in LDL-C after consumption of five servings of black tea daily by mildly hypercholesterolaemic adults; fasting serum TAG levels were slightly higher and HDL-C levels were unchanged (220) . Very recent work has focused on the possible activity of green tea and its constituent epigallocatechin gallate on insulin secretion and the obesity-related insulin resistance syndrome.…”
Section: Teamentioning
confidence: 99%